Coordinated linear beamforming in downlink multi-cell wireless networks - Venturino, L.; Prasad, N.; Xiaodong Wang (2008 42nd Asilomar Conference on Signals, Systems and Computers, 2008)
We consider the problem of co-channel interference mitigation in a downlink multi-cell wireless network. Assuming that each access point serves multiple single-antenna mobiles via space division multiple access (SDMA), we jointly optimize the linear beam-vectors across a set of coordinated cells and resource slots: the objective function to be maximized is the weighted system sum-rate subject to per-base-station power constraints. After deriving the general structure of the optimal beam-vectors, a novel iterative algorithm is presented which attempts to solve the Karush-Kuhn-Tucker (KKT) conditions of the non-convex primal problem at hand. Simulation results are provided to assess the performance of the proposed algorithm.